Strategic Design for the Development of UMKM Management in Improving the Economy of Communities on the Mekong River-Vietnam - Bulutoding, Lince; Iwang, Baso; Sahban, Azizah; Sari, Nur Rahma; Jannah, Raodahtul; Fadhilatunnisa, Della; Fajrin, Farid; Suhartono, Suhartono; Syariati, Namla Elfa; Muslimah, Firanti; Ahmad, Angriani (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyse the design of development strategies for the management of Micro, Small and Medium Enterprises (MSMEs) in the Mekong River region of Vietnam and their impact on the local economy. A qualitative approach was used through FGDs and site surveys to understand the location patterns of MSMEs and the factors that influence their success in improving community welfare. The results show that strategic geographic location, taking into account accessibility, resource availability, and government policy support, plays an important role in determining policies to improve MSMEs' operational efficiency and expand markets. However, challenges such as limited access to capital, lack of access to banking and lack of managerial skills hinder the development of MSMEs in the region.